A novel processing method based on the 3-spot diode laser source for the laser cladding of stainless-steel ball valves. (September 2021) - Lin, Xingchen; Wang, Pengfei; Zhu, Hongbo; Song, Ziqi; Zhang, Yawei; Ning, Yongqiang
Highlights: A 3-spot processing method is introduced for cladding stainless-steel ball valves. Cladding of stainless-steel ball valves are completed with Ni60 + WC powder. Cladded samples are free from any defects such as cracks and pores. Abstract: In this paper, aiming to solve the problem of cracks in the laser cladding for stainless-steel ball valves, a novel method for defect-free processing is introduced. To realize this method, a 3-spot high-power diode laser source is developed. These three spots are respectively used for dynamic local preheating, laser cladding processing and dynamic local tempering. Using this high-power diode laser, a cladding processing of the stainless-steel ball valve with Ni60 + WC powder is successfully completed. Compared with the traditional processing approach, the cladded sample is free from any defects such as cracks and pores, which demonstrates the processing effect of this approach. This work provides a new method for the laser cladding of stainless-steel ball valves.